2017
DOI: 10.3390/s17020370
|View full text |Cite
|
Sign up to set email alerts
|

CSAC Characterization and Its Impact on GNSS Clock Augmentation Performance

Abstract: Chip Scale Atomic Clocks (CSAC) are recently-developed electronic instruments that, when used together with a Global Navigation Satellite Systems (GNSS) receiver, help improve the performance of GNSS navigation solutions in certain conditions (i.e., low satellite visibility). Current GNSS receivers include a Temperature Compensated Cristal Oscillator (TCXO) clock characterized by a short-term stability (τ = 1 s) of 10 −9 s that leads to an error of 0.3 m in pseudorange measurements. The CSAC can achieve a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…where ( , ) t t Dρ − τ are the increments of geometric distances between the receiver and the satellite; 1 r A is the rate of clock of GNSS receiver, which generates a random process such as "white noise" ( ) t ω (Enric, Calero, & Parés, 2017;Krawinkel & Schön, 2015); DΣ is the total increment of errors due to atmospheric delays, multipath effect, and measurement noise.…”
Section: Theoretical Partmentioning
confidence: 99%
See 3 more Smart Citations
“…where ( , ) t t Dρ − τ are the increments of geometric distances between the receiver and the satellite; 1 r A is the rate of clock of GNSS receiver, which generates a random process such as "white noise" ( ) t ω (Enric, Calero, & Parés, 2017;Krawinkel & Schön, 2015); DΣ is the total increment of errors due to atmospheric delays, multipath effect, and measurement noise.…”
Section: Theoretical Partmentioning
confidence: 99%
“…where c is the speed of light, c ≈ 3×10 8 m/s. The relative clock instability for quartz frequency oscillators with temperature compensation used in GNSS geodesic receivers with clock instability of 10 −9 (Enric et al, 2017;Krawinkel & Schön, 2015 ) that at surveillance sam- Figure 1. GSPG network and O. P. Suchkov Standard Spatial Basis (SSB) of the SSUGT ple rate Dt = 15 sec will lead to an error in the increment of the phase pseudoranges F δD = 4.5 m (linear measure).…”
Section: Theoretical Partmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated receiver clock offsets for static Precise Point Positioning (PPP) tests were around 32, 33, and 18 nanoseconds from GPST, GLONASST, and BDT, respectively. In [14], Fernandéz et al presented an analysis of the correlation between temperature and clock stability noise and the impact of its proper modeling on the holdover recovery time and on the positioning performance. They found that fine clock coasting modeling leads to an improvement in vertical positioning precision of around 50% with only three satellites; an increase in the navigation solution availability was also observed; a reduction of holdover recovery time from dozens of seconds to only a few could be achieved.…”
Section: Introductionmentioning
confidence: 99%